Thromboprophylaxis for Hip Revision Arthroplasty: Can We Use the Recommendations for Primary Hip Surgery? A Cohort Study (2019)
The risk of thromboembolic events after hip revision arthroplasty might be higher than in primary hip arthroplasty. However, evidence regarding the use of thromboprophylaxis in revisions is scarce. The purpose of this study is to determine whether thromboprophylaxis recommendations for primary arthroplasty produce similar results in hip revision arthroplasty. This comparative cohort study retrospectively analyzed consecutive patients undergoing primary hip arthroplasty and hip revision surgery between March 2004 and December 2015, who received thromboprophylaxis according to local clinical practice guidelines for primary hip arthroplasty. The prevalence of deep vein thrombosis and pulmonary embolism and the presence of major bleeding events were assessed during hospitalization and at 3 months after discharge and compared between groups. The overall prevalence of thromboembolic events in the hip revision surgery cohort and in the primary hip cohort was 1.62% and 1.35%, respectively (P =.801). The 38.4% of hip revision patients and 20.3% of primary hip patients presented major bleeding events. Thromboembolic disease outcomes with the use of a standardized thromboprophylaxis regimen were similar in both cohorts, regardless of the high variability of hip revision surgery and the increased risk of complications. Implementation of this regimen is recommended in patients requiring joint replacement revision surgery. © The Author(s) 2019.